A Pilot Study into the Periphery Somatic perceptions of Literary Translation: Phenomenological Insights from Cognitive Translatology (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
Norman N. Holland's seminal work Literature and the Brain (2009) delves into how our cognitive processes influence our understanding of literature. Expanding upon this inquiry, this research explores the somatic perceptions of literary translators and their impact on the translation process and resultant text. Grounded in translation process research (henceforth TPR), we interviewed six literary translators from Jordan and analysed their responses thematically. The findings illuminate the significant role of translators' emotional and intuitive emotions in shaping thematic and narrative decisions, yielding a nuanced and subjective target text. Acknowledging the significance of somatic perceptions highlights the personalised nature of literary translation. This study contributes to TPR by advocating for a balanced consideration of individuality alongside the pursuit of generalizability. It also advocates for a contextualised approach in Translation Studies, emphasising the importance of situational realities. In the realm of TPR, our study aligns with cognitive translatology (another branch of TPR alongside computational translatology), emphasising the human element in translation over computational approaches.
Keywords: literary translation; Translation Process Research; generalisability; individuality